Insight into the structural, thermal and ion transport properties of solid and liquid Mg3N2: a model potential and NPT molecular dynamics simulation - Aydin, Yenal; Gunay, Seckin D.; Akdere, Unsal; Tasseven, Cetin (TAYLOR & FRANCIS LTD, 2022)
A model potential has been developed for magnesium nitride (Mg3N2) by fitting the parameters to an experimental lattice constant and bulk modulus. The mechanical properties have been calculated at 0 K. The potential was tested by molecular dynamics simulation at constant number, volume and energy ensemble at 300 K. The structural, ion transport and thermodynamic properties were investigated at a constant number and pressure-temperature ensemble between 300 and 2500 K. The simulated XRD diffractogram at 300 K shows that the crystalline peaks with corresponding (hkl) planes are correctly reproduced. A solid-liquid transition occurs at about 1800 K with a marked variation in all calculated physical properties. The potential successfully models the interactions in Mg3N2 at the solid and liquid phases. The results presented in this paper fill the gap of theoretical study in literature and extend our knowledge further, which could be useful to pave the way for the search of functional materials.
Keywords: Magnesium nitride; model potential; physicochemical properties; molecular dynamics simulation; HYDROGEN-STORAGE; METAL NITRIDES; CRYSTAL; PROGRAM; LI3N; Chemistry; Physics